The Analysis of Production Function and Allocative Efficiency of Seed Water Spinach in Sumurcinde Village Soko District Tuban Regency - Yuli Lestiarini; Darsan Darsan; Fina Sulistiya Ningsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Farmers employ several production variables that affect the quantity of Seed Water Spinach in the cultivation of Seed Water Spinach. This study aims to determine the production factors that affect Seed Water Spinach farming and the level of allocative efficiency of Seed Water Spinach production inputs in Sumurcinde Village, Soko District, Tuban Regency. Sixty-seven farmers were included in the study's sample size, and primary and secondary data were utilised. The variables used include seeds (X1), phonska fertiliser (X2), urea fertiliser (X3), power grow fertiliser (X4), pesticides (X5) and labour (X6). The analysis method used is Coubdoglas function analysis to see which factors affect the production of Seed Water Spinach. Meanwhile, the efficiency of production inputs will be analysed using allocative efficiency analysis. The results were partially Powergrow (X4) significantly affected Seed Water Spinach production. In contrast, Seed (X1), Phoska fertiliser (X2), urea fertiliser (X3), Pesticide (X5) and Labor (X6) did not have a significant effect on seed Seed Water Spinach production. According to the allocative efficiency analysis, using power-grow fertiliser has not been practical, so more power-grow fertiliser must be used to maximise Seed Water Spinach's output.